Girl in the pandemic transnational perspectives. (E-CONTENT GENERIC VENDOR, 2023)
The Girl in the Pandemic: Transnational Perspectives is a collection of essays that explores the experiences of girls and young women during the COVID-19 pandemic in eight different countries. The book highlights the challenges that girls face, such as increased risk of violence, reduced access to education, and mental health problems. However, it also showcases the resilience and strength of girls, who have found new ways to learn, connect with others, and support themselves and their communities.